A Toolbox to Investigate the Impact of Impaired Oxygen Delivery in Experimental Disease Models - Hof, Stefan; Marcus, Carsten; Kuebart, Anne; Schulz, Jan; Truse, Richard; Raupach, Annika; Bauer, Inge; Flögel, Ulrich; Picker, Olaf; Herminghaus, Anna; Temme, Sebastian (Frontiers in Medicine, 2022)
Impaired oxygen utilization is the underlying pathophysiological process in different shock states. Clinically most important are septic and hemorrhagic shock, which comprise more than 75% of all clinical cases of shock. Both forms lead to severe dysfunction of the microcirculation and the mitochondria that can cause or further aggravate tissue damage and inflammation. However, the detailed mechanisms of acute and long-term effects of impaired oxygen utilization are still elusive. Importantly, a defective oxygen exploitation can impact multiple organs simultaneously and organ damage can be aggravated due to intense organ cross-talk or the presence of a systemic inflammatory response. Complexity is further increased through a large heterogeneity in the human population, differences in genetics, age and gender, comorbidities or disease history. To gain a deeper understanding of the principles, mechanisms, interconnections and consequences of impaired oxygen delivery and utilization, interdisciplinary preclinical as well as clinical research is required. In this review, we provide a “tool-box” that covers widely used animal disease models for septic and hemorrhagic shock and methods to determine the structure and function of the microcirculation as well as mitochondrial function. Furthermore, we suggest magnetic resonance imaging as a multimodal imaging platform to noninvasively assess the consequences of impaired oxygen delivery on organ function, cell metabolism, alterations in tissue textures or inflammation. Combining structural and functional analyses of oxygen delivery and utilization in animal models with additional data obtained by multiparametric MRI-based techniques can help to unravel mechanisms underlying immediate effects as well as long-term consequences of impaired oxygen delivery on multiple organs and may narrow the gap between experimental preclinical research and the human patient.